Analisis Matlak Dalam Penentuan Awal Bulan Hijriah Perspektif Ilmu Falak - Haekal Fikri Haekal; Muh. Rasywan Syarif; Andi Intan Nur Cahyani (HISABUNA: Jurnal Ilmu Falak, 2023)
The determination of the beginning of the Hijri month has the term matlak, but what is the background for the emergence of the term matlak and the difference in the unification of matlak for determining the beginning of the Hijri month in astronomy. The type of research used is library research with an astronomical and syar'i research approach, supplemented by primary data and secondary data. Processing and analysis of data through the process of editing data, transforming data and presenting data. The results of this study found that the context of the emergence of the term matlak to determine the beginning of the Hijri month is found in the hadith of Muslim narrations about the incident between Kuraib and Ibnu. Astronomically, differences are caused by differences in latitude and longitude of an area, matlak unification is contained in the principle of matlak unity. The implication of this research is that the matlak phenomenon is widely studied because it is very influential in determining when the Hijri month begins or ends.